Obszary Natura 2000 a złoża węgla brunatnego w Dorzeczu Odry = The Nature 2000 areas and lignite deposits on Odra Basin - Ptak, Miranda (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article presents the current state of setting Nature 2000 areas in Poland together with lignite deposits in Odra Basin located in these areas. The most recent law regulations are presented. Furthermore, problems that come with assessment of mining activity in Nature 2000 areas are emphasized.
Keywords: górnictwo odkrywkowe; Natura 2000; złoża węgla brunatnego; Dorzecze Odry; opencast mining; Odra Basin; lignite deposits